CHEMICAL HEAT-PUMP BASED ON DEHYDROGENATION AND HYDROGENATION OF I-PROPANOL AND ACETONE - KIM, TG; YEO, YK; SONG, HK (JOHN WILEY & SONS LTD, 1992)
A chemical heat pump, based on the reversible reaction couple of the i-propanol-acetone system, was investigated experimentally. The endothermic dehydrogenation of i-propanol occurred at 80-degrees-C with a Raney nickel catalyst suspended in the liquid phase. The unreacted i-propanol was separated from gaseous products in a condenser. The exothermic hydrogenation reaction of the acetone was performed at 200-degrees-C and 1atm, in the presence of the Raney nickel catalyst. The positive value (DELTAG) of the change of Gibbs free energy can make the dehydrogenation reaction of i-propanol rather difficult. This problem can, though, be overcome by the continuous removal of gaseous acetone and hydrogen products from the reaction medium. The dehydrogenation rate equation of i-propanol was obtained as V = 0.1 C(P)A/(1 + 7.0 C(A)). The gas phase hydrogenation reaction of acetone was performed in an exothermic tubular reactor. In order to estimate energy efficiency, a simulation of the separation stage was performed. Based on these experimental and simulation results, the optimal design specifications for the chemical heat pump were determined. The maximum hydrogenation of acetone was obtained when the mole ratio of acetone to hydrogen was 4.0. Energy efficiency was increased when the conversions of hydrogenation and dehydrogenation increased.